The confused taxonomy of Cryptospoidium - Pérez-Cordón, Gregorio (2006)
The last discoveries in the Cryptosporidium biology and phylogenetics reinforce the necessity of a exhaustive review of both life cycle and taxonomy of this parasite. Besides in vitro and in vivo studies, further molecular and genetic studies will allow to advance in the thorough knowledge of this interesting parasite.